Advances in triterpene drug discovery - Goddard, Zoë R; Searcey, Mark; Osbourn, Anne (Trends in pharmacological sciences (Regular ed.), 2024)
AbstractTriterpenes are structurally complex natural products with promising therapeutic properties. Recalcitrance to chemical synthesis has hindered their use in drug development. Recent advances now make it possible to access and harness triterpene structural diversity using engineering biology approaches, enabling the discovery and optimisation of a new generation of drug leads.